An evaluation of procedures to increase cooperation related to hoarding in an older adult with dementia. Issue 2 (17th April 2014) - Donaldson, Jeanne M.; Trahan, Maranda A.; Kahng, SungWoo
<x xml:space="preserve">Abstract</x> The prevalence of hoarding (collection of and refusal to discard unneeded items) is higher in older adults than the general population and has been correlated with dementia. Treatments to increase cooperation with discarding hoarded items have not been systematically evaluated. This study evaluated two procedures for increasing cooperation with handing over hoarded items in an older adult with dementia. The antecedent‐based intervention effectively increased cooperation.